Micro-Doppler Photoacoustic Effect and Sensing by Ultrasound Radar - Gao, Fei (2016)
In recent years, photoacoustics have been studied for both anatomical and functional biomedical imaging. However, the physical interaction between photoacoustic-generated endogenous waves and an exogenously applied ultrasound wave is a largely unexplored area. Here, we report the initial results about the interaction of photoacoustic and external ultrasound waves leading to a micro-Doppler photoacoustic (mDPA) effect, which is experimentally observed and consistently modeled. It is based on a simultaneous excitation on the target with a pulsed laser and continuous wave (CW) ultrasound. The thermoelastically induced expansion will modulate the CW ultrasound and lead to transient Doppler frequency shift. The reported mDPA effect can be described as frequency modulation of the intense CW ultrasound carrier through photoacoustic vibrations. This technique may open the possibility to sensitively detect the photoacoustic vibration in deep optically and acoustically scattering medium, avoiding acoustic distortion that exists in state-of-the-art pulsed photoacoustic imaging systems.